2019
DOI: 10.1002/adma.201903104
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Side Chains on the Charge Mobilities and Functionalities of Semiconducting Conjugated Polymers beyond Solubilities

Abstract: Recent decades have witnessed the rapid development of semiconducting polymers in terms of high charge mobilities and applications in transistors. Significant efforts have been made to develop various conjugated frameworks and linkers. However, studies are increasingly demonstrating that the side chains of semiconducting polymers can significantly affect interchain packing, thin film crystallinity, and thus semiconducting performance. Ways to modify the side alkyl chains to improve the interchain packing order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
171
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(174 citation statements)
references
References 192 publications
(281 reference statements)
3
171
0
Order By: Relevance
“…Both polymers containing the more synthetically complex 5DH sidechains exhibited lower performance than their simpler 2DT analogs when annealed at 100 °C, by a factor of 3 for the T2 polymers and almost an order of magnitude for the TVT polymers. We note that although most studies have found that moving the branching point further away from the conjugated polymer backbone resulted in reduced π–π stacking distance in agreement with these results, [ 41–45 ] this has not always correlated to an improved charge carrier mobility, as observed here. [ 42,52,53 ] Several studies have also highlighted a pronounced odd–even effect with regard to the length of the spacer chain between the backbone and the branching point.…”
Section: Resultssupporting
confidence: 76%
“…Both polymers containing the more synthetically complex 5DH sidechains exhibited lower performance than their simpler 2DT analogs when annealed at 100 °C, by a factor of 3 for the T2 polymers and almost an order of magnitude for the TVT polymers. We note that although most studies have found that moving the branching point further away from the conjugated polymer backbone resulted in reduced π–π stacking distance in agreement with these results, [ 41–45 ] this has not always correlated to an improved charge carrier mobility, as observed here. [ 42,52,53 ] Several studies have also highlighted a pronounced odd–even effect with regard to the length of the spacer chain between the backbone and the branching point.…”
Section: Resultssupporting
confidence: 76%
“…The low-bandgap conjugated polymer's side chain materials demonstrated excellent mechanical properties and acceptable electronic performances. [257,258] In addition to the utilization of polymers with side chains in molecular structures, copolymers, which enable the combination of different functional monomers, drew the attention of researchers for performance optimizations. By integrating biodegradable materials into the block of stretchable semiconducting materials, researchers have fabricated FET sensors with optimized detecting performances.…”
Section: Materials Development For F-fet Sensorsmentioning
confidence: 99%
“…The low‐bandgap conjugated polymer's side chain materials demonstrated excellent mechanical properties and acceptable electronic performances. [ 257,258 ]…”
Section: Strategies Toward the Optimization Of F‐fet Sensorsmentioning
confidence: 99%
“…To solve this problem, an effective strategy is to introduce side chains with large spatial structures or rigid structures to obtain polymers with stronger fluorescence in solid state, in which the space‐crowded structure helps weaken the ACQ effect by inhibiting the strong intermolecular interactions. At the same time, side chain modification is also an effective method to adjust morphology . For instance, Bao et al.…”
Section: Introductionmentioning
confidence: 99%